2021
DOI: 10.4103/ija.ija_124_20
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of direct observation of procedural skills (DOPS) as a formative assessment tool during postgraduate training in anaesthesiology

Abstract: Background and Aims: Formative assessment of procedural skills of Anaesthesiology postgraduate (PG) students is not conducted conventionally. Direct observation of procedural skills (DOPS) helps to identify gaps in performance and provides structured feedback. The present study was taken to explore perceptions of PG students and faculty about DOPS. Methods: This mixed design interventional study was conducted on 12 PGs and 10 faculty members in Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…This is consistent with the other studies that showed similar feedbacks (Zainab Shafiq et al, 2019). As most of other studies also, DOPS satisfaction and practicality in this study were reported as favorable (Bangal, 2018;Jui and Shilpa, 2021;McLeod et al, 2011;Wilkinson et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is consistent with the other studies that showed similar feedbacks (Zainab Shafiq et al, 2019). As most of other studies also, DOPS satisfaction and practicality in this study were reported as favorable (Bangal, 2018;Jui and Shilpa, 2021;McLeod et al, 2011;Wilkinson et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…This study also found an association between progressive DOPS practices and improved trainees' performance as many comparable finding showed similar results (Lörwald et al, 2018;Jui and Shilpa, 2021). Furthermore, major challenges to implement this method of assessment met by participants of this study included lack of awareness and work overload.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“… 14 It has been successfully applied by Siau K and others to assess skills related to gastroscopy and colonoscopy. 15 , 16 Lagoo JY and colleagues introduced DOPS as a formative assessment tool during anaesthesia residency training, 17 and Ali L and his team validated its effectiveness in urological surgery resident training. 18 While DOPS is extensively used in nursing abroad, 19 , 20 its application in nursing skills is still in the early exploration stage in China, with limited use in specialized nursing skill evaluation.…”
Section: Introductionmentioning
confidence: 99%